Drug–drug interaction potential and clinical pharmacokinetics of enerisant, a novel potent and selective histamine H3 receptor antagonist. (3rd July 2021) - Terasaka, Shuichi; Hachiuma, Kenji; Mano, Yoko; Onishi, Koichi; Kitajima, Iwao; Nishino, Izumi; Endo, Hiromi
Abstract: We evaluated the in vitro drug–drug interaction (DDI) potential of enerisant (TS-091), a histamine H3 receptor antagonist/inverse agonist, mediated by cytochrome P450 (CYP) and transporters, as well as the pharmacokinetics of enerisant in healthy male subjects. Enerisant did not inhibit CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, or CYP3A4 and did not induce CYP1A2, CYP2B6, or CYP3A4. Enerisant inhibited organic cation transporter 2, multidrug and toxin extrusion protein (MATE) 1, and MATE2-K, but not P-glycoprotein (P-gp), breast cancer resistance protein, organic anion transporting polypeptide (OATP) 1B1, OATP1B3, organic anion transporter (OAT) 1, or OAT3. Enerisant was a substrate for P-gp, but not for eight other transporters. In healthy male subjects, enerisant was rapidly absorbed after oral administration, and the plasma concentration increased dose-dependently. The urinary excretion of enerisant within 48 h after administration was 64.5% to 89.9% of the dose, indicating that most of the absorbed enerisant was excreted in the urine without being metabolized. Based on the plasma concentrations at the estimated clinical dose, enerisant is unlikely to cause CYP-mediated, clinically relevant DDI. Although the possibility of transporter-mediated, clinically relevant DDI cannot be ruled out, there is little or no risk of side effects.